Structural, electronic and magnetic properties of ferromagnetic perovskites : a comparative study - Thomas, Rhian-Mari (Trinity College (Dublin, Ireland). School of Physics, 2001)
During the course of this research work, the physical properties of twelve mixed-valence manganites have been investigated and compared. Upon embarking on this project, the prospect of incorporating these newly re-discovered "colossal magnetoresistance" materials in future device applications, provided the impetus for determining which principal factors govern their ferromagnetic ordering temperatures, Tc, and thus optimising this value through judicious chemical substitution.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin